MANAGING THE FORMATION OF REGIONAL INNOVATIVE INFRASTRUCTURE - C. Б. Колодинський; О. В. Захарченко; М. А. Заєць (Ринкова економіка: сучасна теорія і практика управління)
Ukraine as a separate and independent country in the form of its state structure, is unitary in its form. Unitarianism (comes from the Latin unitare - unity), expresses in the dominance of centralized state power and control over other subjects of the state. Along with this, Ukraine has identified and developed a scientifically based regional policy in which emphasis is placed on enhancing democratic self-governance and governance of each individual region in its organic integration links with other regions horizontally and vertically by government agencies. Such relations between state and regional authorities should be based on the rules of law that are recorded in the Constitution of Ukraine.